2018
DOI: 10.1017/ice.2018.148
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection after kidney and pancreas transplantation

Abstract: Organ/space SSIs remain a serious and common complication after SPK and PAK. Prolonged cold ischemic time and SPK transplant were the risk factors predictive of SSIs. Appropriate perioperative prophylaxis in high-risk patients targeting the potential pathogens producing SSIs in kidney and/or pancreas transplant recipients and a reduction in cold ischemia may prove beneficial in reducing these SSIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
4
16
2
Order By: Relevance
“…The incidence of SSIs was often higher in prior studies ranging between 20% and 50% [5][6][7]12], a single study reported SSIs at a lower frequency with 14% for SPK-Tx and 9% for pancreas after kidney transplantation [13]. One explanation for these differences could be that most studies used older data compared to the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The incidence of SSIs was often higher in prior studies ranging between 20% and 50% [5][6][7]12], a single study reported SSIs at a lower frequency with 14% for SPK-Tx and 9% for pancreas after kidney transplantation [13]. One explanation for these differences could be that most studies used older data compared to the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Risk factors for SSIs were assessed with univariable and multivariable logistic regression. Based on findings from a previous study [5], we decided to include cold ischemia time and the transplant procedure (SPK-Tx vs. P-Tx) in the multivariable model. The duration of hospitalization in patients with and without SSI was compared with the Wilcoxon-Rank test.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed graft function refers to the incidence of acute kidney injury in the first week of kidney transplantation which necessitates a dialysis intervention [24]. Definitions of SSI, graft rejection, and graft failure were inconsistent with the diagnostic criteria that were applied in the original studies [3,25,26]. Reviews, editorials, preclinical studies, and single-arm studies without an OKT control group were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…Since the initial successful case in 1954, conventional open kidney transplant (OKT) surgery with anastomosis of the graft vessels to the recipient's iliac vessels has become the standard procedure [2]. However, OKT has been associated with a higher risk of wound complications [3], particularly in recipients with obesity, diabetes, critical illness, and immunosuppression [4][5][6]. Moreover, the relatively larger incision of OKT has been recognized as an important cause of surgical site infection (SSI) after the surgery [7].…”
Section: Introductionmentioning
confidence: 99%